Flowering and fruiting responses to climate change of two Arctic plant species, purple saxifrage (Saxifraga oppositifolia) and mountain avens (Dryas integrifolia) - Panchen, Zoe; Gorelick, Root (NRC Research Press (a division of Canadian Science Publishing), 2015)
In temperate regions there are clear indications that spring flowering plants are flowering earlier due to rising temperatures of contemporary climate change. Temperatures in temperate regions are rising predominantly in spring. However, Arctic regions are seeing unprecedented temperature increases, predominantly towards the end of the growing season. We might, therefore, expect to see earlier flowering of later-season flowering Arctic plants. Parks Canada has been monitoring purple saxifrage (Saxifraga oppositifolia) and mountain avens (Dryas integrifolia) flowering and fruiting times for 20 years at Tanquary Fiord, Quttinirpaaq National Park, Ellesmere Island. S. oppositifolia flowers in early spring, while D. integrifolia flowers in mid-summer. Over the 20 year period, Tanquary Fiordâ s annual and late-summer temperatures have risen significantly. During the same timeframe, D. integrifolia showed a trend towards earlier flowering and fruiting, but S. oppositifolia showed no changes in flowering or fruiting time. Flowering time was related to monthly temperatures just prior to flowering. The number of flowers produced was related to the previous autumnâ s monthly temperatures. We found no relationship between flowering time and snow melt date. Our findings suggest that Arctic community-level ecological effects from climate change induced phenology changes will differ from those in temperate regions. The accepted manuscript in pdf format is listed with the files at the bottom of this page. The presentation of the authors' names and (or) special characters in the title of the manuscript may differ slightly between what is listed on this page and what is listed in the pdf file of the accepted manuscript; that in the pdf file of the accepted manuscript is what was submitted by the author.